Gastrointestinal adverse events associated with tirzepatide: A bibliometric and pharmacovigilance analysis - Peng Shen; Meng-si Peng; Sun Jo Kim; Kyung-In Joung; Kwang Joon Kim (PLoS ONE, 2026)
Background This study examines gastrointestinal adverse events (GIAEs) associated with tirzepatide using bibliometric and pharmacovigilance analyses. Research design and methods A bibliometric analysis of Web of Science data identified research trends in tirzepatide-related adverse events, while a pharmacovigilance analysis of FAERS data (Q2 2022–Q2 2024) assessed real-world GIAEs patterns. Disproportionality, time-to-onset, univariate, and comparative analyses were conducted to evaluate reporting odds ratios (RORs), onset timing, and subgroup differences. Results Among 110 studies, cardiovascular outcomes predominated as the research focus. FAERS data showed that nausea (27.7%) and diarrhea (12.8%) were the most frequently reported events, whereas eructation and impaired gastric emptying had the highest disproportionality. GIAEs were more common in older adults, males, and patients receiving concomitant medications, and most occurred within 3 months (median onset: 16 days). Tirzepatide had a lower ROR for GIAEs than GLP-1 receptor agonists but a higher ROR than non-GLP-1 drugs, with a greater risk in patients with type 2 diabetes (T2DM) than in those using tirzepatide for weight loss. Conclusion Tirzepatide is associated with an increased risk of GIAEs, particularly among patients with T2DM, males, older adults, and those using concomitant medications. FAERS-based real-world evidence complements clinical trial data and highlights the need for individualized patient monitoring and management strategies.